ENHANCING COMMUNITY CLINICAL PHARMACY STUDENTS’ RECOUNT WRITING SKILL THROUGH THE “EARTH SONG” VIDEO CLIP AT STIKES WIDYA DHARMA HUSADA TANGERANG - Anggraini Karditiawati (Cakrawala Pedagogik, 2023)
The study's objectives were to ascertain how the teacher enhanced the recount writing abilities of community clinical pharmacy students at STIKes Widya Dharma Husada Tangerang by having them to watch the "Earth Song" video clip and to assess how much their writing abilities had improved both before and after. Based on the problem regarding the lack of students’ knowledge and interesting media to share ideas in writing. A pre-test and post-test control group design was utilized by the researcher as a quantitative method using a true experimental approach. The respondents were 64 of first semester community clinical pharmacy students, and they were divided into two classes, 01FKKP008 as the experimental class and 01FKKP007 as the control class. In the experimental class, the researcher taught recount writing by using the video clip, whereas in the control class, only the conventional method was used. The result showed that the experimental group's mean score increased from 41.81 to 81.59, while the control group's score went up from 37.31 to 58.93. It can be concluded that teaching recount writing through the "Earth Song" video clip has been implemented appropriately, as evidenced by the fact that the score of the experimental class was higher than that of the control class. As a result, the video clip was an effective medium to be used in enhancing recount writing skills.